2020
DOI: 10.1101/2020.04.09.20059154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 pandemic in the African continent: Forecasts of cumulative cases, new infections, and mortality

Abstract: Background:The epidemiology of COVID-19 remains speculative in Africa. To the best of our knowledge, no study, using robust methodology provides its trajectory for the region or accounts for local context. This paper is the first systematic attempt to provide prevalence, incidence, and mortality estimates across Africa.Methods: Caseloads and incidence forecasts are from a co-variate-based instrumental variable regression model. Fatality rates from Italy and China were applied to generate mortality estimates af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 31 publications
5
58
1
1
Order By: Relevance
“…Although several studies have looked at the spread of COVID-19 in African countries [34][35][36][37][38] , we are only aware of one other modelling study which considers the impact of different interventions on the spread of COVID-19 in Africa. Walker et al 39 used a similar SEIR model and predicted a near 90% reduction in cases for sub-Saharan Africa assuming a 75% reduction in contacts starting at an incidence of 0.2 deaths per 100,000 population per week and sustained over the first 250 days of an epidemic.…”
Section: Main Findingsmentioning
confidence: 99%
“…Although several studies have looked at the spread of COVID-19 in African countries [34][35][36][37][38] , we are only aware of one other modelling study which considers the impact of different interventions on the spread of COVID-19 in Africa. Walker et al 39 used a similar SEIR model and predicted a near 90% reduction in cases for sub-Saharan Africa assuming a 75% reduction in contacts starting at an incidence of 0.2 deaths per 100,000 population per week and sustained over the first 250 days of an epidemic.…”
Section: Main Findingsmentioning
confidence: 99%
“…new cases data have fitted the ARIMA (0,1,0), ARIMA (0,1,0), and ARIMA (0,1,14) models, increase from April to May and a 39% increase from May to June, which suggests a possible slowing down of the pandemic with time [5].…”
Section: Discussionmentioning
confidence: 97%
“…As of 6 September 2020 at 1:00 pm, 27,087,151 total cases of COVID-19 have been reported, including 884,110 total deaths with a 3.3% fatality rate and 19,208,336 total recovered with a 70.9% recovered rate and also 6,994,705 active cases with a 25.8% rate as Worldometers information provided globally. In Africa, as this report showed that the total cases were 1,297,434 with 4.8% covered from the world, total deaths were 31,131 with a 2.4% of fatality rate, totally recovered was 1,033,859 with a 79.7% of recovery rate, and active cases was 232,444 with 17.9% rate [3][4][5]. And, the current Worldometer information statistics were summarized clearly in table 1 below.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations